Factors influencing purchasing decision of online bakery course among Via Facebook Fan page in Thailand. - Liangjaroensuk, Lapassawee (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
This research aimed to study the marketing mix (6 P’s) which influence a consumer decision to buy bakery courses online via Facebook in Thailand. For this study, the independent variables were demographic factors including gender, age, educational level, occupation, income and the digital marketing mix factors including product, price, place, promotion, personalization, privacy. The research samples were 400 members of bakery society facebook Fan page. Data were collected by using the questionnaire. The statistical methods used in data analysis were percentage, mean, standard deviation, t-test, One-Way ANOVA and multiple regression analysis. The results of hypothesis test showed that the demographic factors including gender, age, education level, occupation, income had not influenced on purchase decisions of online bakery course via facebook Fan page. Moreover, the digital marketing mix (6 P’s) including promotion, price, product and place influenced the decision making to buy bakery courses online via Facebook in Thailand with a statistical significance level of 0.01. Article history : Received 20 June 2019 Revised 19 August 2019 Accepted 21 August 2019 SIMILARITY INDEX = 0.96 %